2016
DOI: 10.1148/radiol.2015150131
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pancreatic Cancer, Disease-specific Mortality, and All-Cause Mortality in Patients with Nonresected IPMNs: A Long-term Cohort Study

Abstract: Five-year PC development, disease-specific mortality, and all-cause mortality were approximately 4%, 2%, and 6% for BD-IPMNs and 46%, 19%, and 19% for MD-IPMNs, respectively. The presence of an MD-IPMN, but not cyst size, was significantly associated with PC development and subsequent mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…A recent study reported that an initial cyst size of 30 mm or above in BD‐IPMN was not associated with development of invasive IPMN or PDAC. In contrast, patients in the present study with primarily large cysts (at least 30 mm) who underwent initial surveillance had an increased risk (29 per cent) of malignant transformation during observation, compared with those with cysts smaller than 20 mm.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study reported that an initial cyst size of 30 mm or above in BD‐IPMN was not associated with development of invasive IPMN or PDAC. In contrast, patients in the present study with primarily large cysts (at least 30 mm) who underwent initial surveillance had an increased risk (29 per cent) of malignant transformation during observation, compared with those with cysts smaller than 20 mm.…”
Section: Discussionmentioning
confidence: 97%
“…Two recent cohorts of non‐operated patients with high‐risk IPMNs deserve discussion. In a study by Nagata and colleagues, among 285 patients initially kept under observation, 13 had main‐duct IPMNs and 41 had branch‐duct IPMNs with cysts of at least 30 mm. In branch‐duct IPMNs overall mortality was higher than disease‐specific mortality.…”
Section: Discussionmentioning
confidence: 99%
“…1). This distinction has clinical relevance because MD involvement has been identified as a predictor of malignant transformation (20)(21)(22)(23). A MD dilation over 9 mm is considered to be a "high-risk stigmata" whereas a dilation comprised between 5-9 mm is considered as a "worrisome feature" for malignancy (24).…”
Section: Introductionmentioning
confidence: 99%